Upaya Perlindungan Hukum Bagi Anak Terhadap Potensi Korban Perdagangan Manusia (Human Trafficking) - Muktar, Muktar; Sheilla Winanda (Jurnal Justice Aswaja, 2023)
This article aims to determine and analyze the legal protection for children against potential victims of human trafficking (Human Tfafficking) based on Law No. 21 of 2007 concerning the Eradication of Criminal Acts of Human Trafficking, and the factors causing the occurrence of criminal acts of children against potential victims of human trafficking (Human Tfafficking). In this case, Human trafficking is one of the criminal acts carried out in a structured manner which is carried out in groups or involves several people who are interrelated and aim to exploit someone in order to gain money or other material benefits, this is done by perpetrators of human trafficking. In relation to this, in line with the position of women and children who are the same as adult men before the law, as a manifestation of equality before the law, bringing consequences to the same responsibility before the law for anyone who commits violations, crimes or other deviant behavior against children. This is in line with efforts to protect women and children legally, one of which is through the prevention and eradication of human trafficking, which needs to be carried out continuously in order to maintain quality human resources based on the provisions of Law Number 21 of 2007 concerning the Eradication of Criminal Acts of Human Trafficking (UU PTPPO).